King Richard II - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"King Richard II" by William Shakespeare is a history play written in 1595. It chronicles the dramatic downfall of England's King Richard II, who ruled from 1377 to 1399. When Richard banishes his cousin Henry Bolingbroke and seizes his inheritance, he sets in motion a conspiracy among the nobility. As Bolingbroke returns with an army to reclaim his lands, Richard faces betrayal, capture, and a public ceremony that will determine the fate of his crown and his life. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Richard_II_(play)
Release date is 1998-10-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: Richard II, King of England, 1367-1400 -- Drama; Tragedies (Drama); Historical drama; Great Britain -- History -- Richard II, 1377-1399 -- Drama